African-Asian encounters new cooperations and new dependencies - Graf, Arndt; Hashim, Azirah (Global Asia (Amsterdam, Netherlands), 2017)
In recent decades, ties between Africa and Asia have greatly increased. And while most of the scholarly attention to the phenomenon has focused on China, often with an emphasis on asymmetric power relations in both politics and economics, this book takes a much broader view, looking at various small and medium-sized actors in Asia and Africa in a wide range of fields. It will be essential for scholars working on Asian-African studies and will also offer insights for policymakers working in this fast-changing field.